FG SGE: THE R CORONAE BOREALIS - TYPE ACTIVITY AND PULSATIONS - Rosenbush, A.; Reszelski, M.; Muyllaert, E. (Одеські астрономічні публікації, 2017)
Using the known connection between pulsations and the deep light decline in stars of the R Coronae Borealis - type variability, the pulsation period of FG Sge is determined, which is now equal to 103 days.